EEG in fitness to drive evaluations in people with epilepsy — Considerable variations across Europe. (July 2020) - Markhus, Rune; Henning, Oliver; Molteberg, Ellen; Hećimović, Hrvoje; Ujvari, Akos; Hirsch, Edouard; Rheims, Sylvain; Surges, Rainer; Malmgren, Kristina; Rüegg, Stephan; Gil-Nagel, Antonio; Roivainen, Reina; et al.
Highlights: Use of EEG in fitness-to-drive evaluations varies considerable in Europe. There is no consensus how EEG pathology should be assessed in driving evaluations. Significance of prolonged reaction times during epileptiform discharges is unclear. More research and international guidelines are needed for driving evaluations. Abstract: Purpose: Epilepsy patients consider driving issues to be one of their most serious concerns. Ideally, decisions regarding fitness to drive should be based upon thorough evaluations by specialists in epilepsy care. In 2009, an EU directive was published aiming to harmonize evaluation practices within European countries, but, despite these recommendations, whether all epileptologists use the same criteria is unclear. We therefore conducted this study to investigate routine practices on how epileptologists at European epilepsy centers evaluate fitness to drive. Methods: A questionnaire was sent to 63 contact persons identified through the European Epi-Care and the E-pilepsy network. The questionnaire addressed how fitness-to-drive evaluations were conducted, the involvement of different professionals, the use and interpretation of EEG, and opinions on existing regulations and guidelines. Results: The questionnaire was completed by 35 participants (56 % response rate). Results showed considerable variation regarding test routines and the emphasis placed on the occurrence and extent of epileptiform discharges revealed by EEG. 82 % of the responders agreed that there was a need for more research on how to better evaluate fitness-to-drive in people with epilepsy, and 89 % agreed that regulations on fitness to drive evaluations should be internationally coordinated. Conclusion: Our survey showed considerable variations among European epileptologists regarding use of EEG and how findings of EEG pathology should be assessed in fitness-to-drive evaluations. There is a clear need for more research on this issue and international guidelines on how such evaluations should be carried out would be of value.